KREATIVITAS NAMIN DALAM PETA PERKEMBANGAN JAIPONGAN BAJIDORAN - Atang Suryaman (LP2M ISBI Bandung, 2018)
The game ofkendangin each typeofperfonnance art has its own peculiarities. First in the context ofkendangaspartofindependentkarawitanwork, then the secondin the kendangcontext as partofthefunctional karaokework which is specificallyin dance music. Each player and drum game has its ownspecificity and capabilities, sothedrummeris apersonwhois required tohave specialskills. Especially inperfonnance artthat requires the ability todo renewal, development and creativity. Oneofthem isintheartofBajidoran-Jaipongan, where inaddition to being united in karawitan, at the same time itis required toserve a dancer (Bajidor). From a series ofkendangplayers and Bajidorangroups that are well knowninthe community, the name Namin and